Preparation of block copolymer self-assemblies via PISA in a non-polar medium based on RCMP - Zheng, Yichao (2024)
Polymerization-induced self-assembly (PISA) is conducted in a non-polar medium (n-dodecane) via reversible complexation-mediated polymerization (RCMP). Stearyl methacrylate (SMA) is used to synthesize a macroinitiator, and subsequent block polymerization of benzyl methacrylate (BzMA) from the macroinitiator in n-dodecane afforded a PSMA-PBzMA block copolymer, where PSMA is poly(stearyl methacrylate) and PBzMA is poly(benzyl methacrylate). Because PSMA is soluble but PBzMA is insoluble in n-dodecane, the block copolymer formed a self-assembly during the block polymerization (PISA). Spherical micelles, worms, and vesicles are obtained, depending on the degrees of polymerization of PSMA and PBzMA. "One-pot" PISA is also attained; namely, BzMA is directly added to the reaction mixture of the macroinitiator synthesis, and PISA is conducted in the same pot without purification of the macroinitiator. The spherical micelle and vesicle structures are also fixed using a crosslinkable monomer during PISA. RCMP-PISA is highly attractive as it is odorless and metal-free. The "one-pot" synthesis does not require the purification of the macroinitiator. RCMP-PISA can provide a practical approach to synthesize self-assemblies in non-polar media.